Liberation movements in power party & state in Southern Africa - Southall, Roger (Boydell & Brewer, 2013)
The liberation movements of Southern Africa arose to combat racism, colonialism and settler capitalism and engaged in armed struggle to establish democracy. After victory over colonial and white minority regimes, they moved into government embodying the hopes and aspirations of their mass of supporters and of widespread international solidarity movements. Even with the difficult legacies they inherited, their performance in power has been deeply disappointing. Roger Southall tracks the experiences in government of ZANU-PF, SWAPO and the ANC, arguing that such movements are characterised by paradoxical qualities, both emancipatory and authoritarian. Analysis is offered of their evolution into political machines through comparative review of their electoral performance, their relation to state and society, their policies regarding economic transformation, and their evolution as vehicles of class formation and predatory behaviour. The author concludes that, while they will survive organizationally, their essence as progressive forces is dying, and that hopes of a genuine liberation throughout the region will depend upon political realignments alongside moral and intellectual regeneration. ANC South Africa. SWAPO Namibia. Zanu-PF Zimbabwe. Roger Southall is Professor Emeritus in Sociology, University of the Witwatersrand and a Research Associate of the Society, Work and Development Institute. Southern Africa: University of KwaZulu-Natal Press
Title from publisher's bibliographic system (viewed on 02 Oct 2015)
Keywords: ZANU-PF (Organization : Zimbabwe); SWAPO.; African National Congress; South-West Africa People's Organization of Namibia; Zimbabwe African National Union; Geschichte 1980-2012; Politik; National liberation movements / Zimbabwe; National liberation movements / Namibia; National liberation movements / South Africa; Regierungspartei; Politische Führung; Parteiprogramm; Südafrika (Staat); Zimbabwe / Politics and government / 1980-; Namibia / Politics and government / 1990-; South Africa / Politics and government / 1994-; Südafrika; Simbabwe